Pemanfaatan Aplikasi Zoom sebagai Media Pembelajaran PAI pada Masa Pandemi Covid-19 di SMPN 1 Karawang Barat - Asep Komarudin Ramdani; Zaenal Arifin; N. Fathurrohman (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
Learning on this day, all over the world, especially in Indonesia experienced a change from previous. The quality of education in this era is facing a challenge as the impact of outbreaks of Covid-19. This research aims to use the App Zoom Cloud Meetings PAI learning media in SMPN 1 Karawang Barat on the pandemic of Covid-19. The subject in this research is the teachers of SMPN 1 Karawang Barat. The instrument used is the utilization of the App Zoom Cloud Meetings as a solution to the learning media PAI on the pandemic of Covid-19. By doing observation, interview and documentation through a qualitative approach. Based on the results of the research that has been conducted can be concluded that the teachers of SMPN 1 Karawang Barat utilize the App Zoom Cloud Meetings as a solution of learning media. The factors supporting and inhibiting in the utilization of the App Zoom Cloud Meetings as a solution of learning media in the pandemic of Covid-19 in SMPN 1 Karawang Barat as follows: a) The supporting Factors in terms of network quality and the ability of teachers to use or operational App Zoom Cloud Meetings. So if the two are related to the learning process carried out to achieve the process of success in under going the learning to the learners. b) Constraints in the use of the App Zoom Cloud Meetings PAI learning media in SMPN 1 Karawang Barat on the pandemic Covid-19, namely in terms of signal disconnected.